2020
DOI: 10.3389/fgene.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Whole-Genome Significant Single Nucleotide Polymorphisms in Candidate Genes Associated With Serum Biochemical Traits in Chinese Holstein Cattle

Abstract: A genome-wide association study (GWAS) was conducted on 23 serum biochemical traits in Chinese Holstein cattle. The experimental population consisted of 399 cattle, each genotyped by a commercial bovine 50K SNP chip, which had 49,663 SNPs. After data cleaning, 41,092 SNPs from 361 Holstein cattle were retained for GWAS. The phenotypes were measured values of serum measurements of these animals that were taken at 11 days after parturition. Two statistical models, a fixed-effect linear regression model (FLM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The biopsied dairy cattle had their fatty liver condition diagnosed according to the average percentage of hepatic cells containing lipid droplets in the tissue, and other background information of these cows including production and serum biochemical indexes [1,60] was shown in Table S2. As a result, six samples were diagnosed as normal liver (6.26 ± 5.23%) and eight as severe fatty liver (86.75 ± 4.83%).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biopsied dairy cattle had their fatty liver condition diagnosed according to the average percentage of hepatic cells containing lipid droplets in the tissue, and other background information of these cows including production and serum biochemical indexes [1,60] was shown in Table S2. As a result, six samples were diagnosed as normal liver (6.26 ± 5.23%) and eight as severe fatty liver (86.75 ± 4.83%).…”
Section: Sample Collectionmentioning
confidence: 99%
“…More than 60% of dairy cows develop fatty liver during the transition period from dry milk to lactation due to negative energy imbalance [1], resulting in weakened liver function and decreased milk production [2]. The fatty liver disease in dairy cows is a typical type of nonalcoholic fatty liver disease (NAFLD), mainly caused by obesity and stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of fatty liver in perinatal dairy cows primarily includes the negative nutrient balance and the accumulation of high level of free fatty acids (FFA) in serum or triglycerides (TAG) deposited in liver [1]. Liver, the central organ of organisms, regulates the metabolic balance of carbohydrate, fat, and protein in mammals [13].…”
Section: Progress Of the Pathogenesis Mechanism Of Fatty Liver Diseasementioning
confidence: 99%
“…Our investigation in the last three years indicated that 48.85% of dairy cows (n = 346) within 2 weeks after parturition were diagnosed with light or severe fatty liver disease by randomly selecting 710 Holstein dairy cows from four commercial farms (Zhang et al, unpublished data) [1,2]. The suspected fatty liver cows and/or normal cows were firstly distinguished by applying the previously reported model [3] using the detected values of serum biochemical traits (glucose, Glu; non-esterified fatty acid, NEFA; aspartate transaminase, AST), then representative cows with different suspected extents were biopsied for liver tissue samples for fat deposition amount assessment by oil red staining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation